2021
DOI: 10.1038/s41467-021-24179-5
|View full text |Cite
|
Sign up to set email alerts
|

PEG-stabilized coaxial stacking of two-dimensional covalent organic frameworks for enhanced photocatalytic hydrogen evolution

Abstract: Two-dimensional covalent organic frameworks (2D COFs) featuring periodic frameworks, extended π-conjugation and layered stacking structures, have emerged as a promising class of materials for photocatalytic hydrogen evolution. Nevertheless, the layer-by-layer assembly in 2D COFs is not stable during the photocatalytic cycling in water, causing disordered stacking and declined activity. Here, we report an innovative strategy to stabilize the ordered arrangement of layered structures in 2D COFs for hydrogen evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 50 publications
3
90
0
Order By: Relevance
“…S24 and Table S2 †). 9,14,19,22,27,28,[31][32][33][34][35][36][37][38] The control experiments indicated that the kinetic curve of the photocatalytic activity was completely inactive in the absence of water or a photocatalyst, suggesting that water and a photocatalyst were essential for the hydrogen evolution reaction and that water was the proton source and not NMP (Fig. S25 †).…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…S24 and Table S2 †). 9,14,19,22,27,28,[31][32][33][34][35][36][37][38] The control experiments indicated that the kinetic curve of the photocatalytic activity was completely inactive in the absence of water or a photocatalyst, suggesting that water and a photocatalyst were essential for the hydrogen evolution reaction and that water was the proton source and not NMP (Fig. S25 †).…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…An appreciable number of organic semiconductors as photocatalysts have been specically targeted to achieve outstanding photocatalytic activity because they have numerous attractive properties, including low-temperature processing, low-cost production, easily adjustable molecular structure, and tunable bandgaps, that differentiate them from their inorganic counterparts. Since graphitic carbon nitride was successfully applied to photocatalytic hydrogen evolution systems in 2009, 1 several research studies using polymeric photocatalysts, 2,3 such as linear conjugated polymers, 4-8 conjugated microporous polymers, 9,10 polymer dots, [11][12][13][14][15] covalent triazine frameworks, [16][17][18] and covalent organic frameworks, [19][20][21][22][23][24] for hydrogen evolution have been gradually published. Recently, a growing body of literature has shown that the incorporation of acceptor units containing sulfonyl groups or phosphine oxide groups into polymer backbones enhances the wettability of polymers through intra-and interchain O-H interactions with water.…”
Section: Introductionmentioning
confidence: 99%
“…A high AQE for H 2 production of 6% at λ = 420 nm was obtained, which was ascribed to the welldefined and ordered structure of CTF-1, as well as low carbonization and superior band positions. In 2021, Chen et al [64] reported the synthesis of four isostructural porphyrinic 2D COFs (MPor-DETH-COF, M = H 2 , Co, Ni, Zn; DETH = 2,5-diethoxyterephthalohydrazide) and their application in photocatalytic H 2 production [Figure 7]. All four COFs have AA stacking structures with high crystallinity and large surface areas.…”
Section: Carbon Nitride-based Photocatalystsmentioning
confidence: 99%
“…Simultaneous defect tuning and surface property optimization generated high concentrations of long-lived electrons and facilitated Reproduced from Ref. [64] with permission from Springer Nature.…”
Section: Nitride-based Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation